Use of [C4mim]Cl for efficient extraction of caffeoylquinic acids from sweet potato leaves - Toyonobu Usuki (Nature Portfolio, 2017)
Abstract Sweet potato, Ipomoea batatas, is a widely cultivated vegetable worldwide. The leaves contain polyphenolic natural products called caffeoylquinic acids (CQAs), which possess biological activities including inhibition of aggregation of amyloid peptides. The present study describes an efficient extraction and isolation procedure for CQAs from sweet potato leaves using a cellulose-dissolving ionic liquid. The results showed that, compared to methanol, use of 1-butyl-3-methylimidazolium chloride ([C4mim]Cl) allowed the extraction of a 6.5-fold greater amount of CQAs. This protocol will enable the efficient extraction of other organic compounds and biopolymers from natural materials.